2015
DOI: 10.1016/j.obhdp.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The prospect of a perfect ending: Loss aversion and the round-number bias

Abstract: Studies across a range of domains have shown that individuals tend to focus on round numbers as cognitive reference points; a so-called left-digit effect. We explain this effect by combining analog numerical heuristics with prospect theory in order to develop an analog value function that predicts the key characteristics of the left-digit effect. Most importantly, this value function predicts an unreported phenomenon, namely; that the left-digit effect will be more pronounced in situations involving losses (cf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In other words, it is loss aversion rather than learning which affects a bidder's behaviour, thus reducing the probability of incurring the winner's curse. While learning is a cognitive process by definition, some research has shown that loss aversion also results from a cognitive process (Fraser-Mackenzie et al 2015;Tom et al 2007). Thus, from this perspective, it is possible to argue that the disappearance of the winner's curse in the €20 auction results from a cognitive process mediated by loss aversion.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, it is loss aversion rather than learning which affects a bidder's behaviour, thus reducing the probability of incurring the winner's curse. While learning is a cognitive process by definition, some research has shown that loss aversion also results from a cognitive process (Fraser-Mackenzie et al 2015;Tom et al 2007). Thus, from this perspective, it is possible to argue that the disappearance of the winner's curse in the €20 auction results from a cognitive process mediated by loss aversion.…”
Section: Resultsmentioning
confidence: 99%
“…Hinrichs et al (1982) examined how subjects use place information in a number task and provided foundational evidence on how the number of digits influences speed and accuracy in understanding a number's value. Fraser-Mackenzie et al (2015) combined loss aversion with the left-digit effect to develop a value function that predicts the key characteristics of LDB. They found support for their theory using a laboratory experiment and observational data.…”
Section: The Left-digit Biasmentioning
confidence: 99%
“…Their analysis was based on Prospect Theory (Kahneman, 1992; Kahneman & Tversky, 1979) and makes the argument that a reference point alters the individual's value function, creating a discontinuity at the reference point. The issue is further analyzed in Fraser‐Mackenzie, Sung, and Johnson (2015). Their article characterizes the phenomenon as the left digit effect (LDE).…”
Section: Literature Reviewmentioning
confidence: 99%